Management of Educational Institutions Integrated Security - Prokofieva, Elena N.; Erdyneeva, Klavdiya G.; Efremova, Dilyara N.; Avilova, Natalia L.; Savina, Elena G. (International Review of Management and Marketing, 2016)
The relevance of the paper is conditioned by the multiple threats for social and personal security in the modern world. The purpose of the paper is aimed at supporting of acceptable security risks in real conditions of educational institutions' functioning. The authors present a dynamic model of educational organizations' complex safety. The leading approaches to the research are integrative, process and personality-activities approaches. The authors have developed the landscape of educational organizations, processes, providing comprehensive security. The priorities of the educational organization's activities in the field of integrated security are presented. This paper is intended for educators, researchers, heads of educational organizations involved in the management of education organizations' complex safety. Keywords: Management, Integrated Security, Educational Organizations, Dynamic Model, Process Landscape. JEL Classifications: I21, I25, I28